2023
DOI: 10.3390/appliedchem3020015
|View full text |Cite
|
Sign up to set email alerts
|

New Physicochemical Methodology for the Determination of the Surface Thermodynamic Properties of Solid Particles

Abstract: The study of the surface thermodynamic properties of solid materials is primordial for the determination of the dispersive surface energy, polar enthalpy of adsorption and Lewis’s acid base properties of solid particles. The inverse gas chromatography technique (IGC) at infinite dilution is the best surface technique for the determination of the surface physicochemical properties of materials. (1) Background: This paper was devoted to studying the surface properties of solid materials, such as alumina, titania… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 81 publications
(123 reference statements)
0
44
0
Order By: Relevance
“…The error committed by the other models relative to the thermal model exceeds 25% with respect of Hamieh model. From Table , by taking the examples of the Kiselev method (γ s d (343.15 K ) = 57.8 mJ/m 2 )) and Hamieh model (γ s d (343.15 K) = 79.3 mJ/m 2 ), one obtained an error equal to . These results clearly showed that the various models that did not consider the change in the surface areas of molecules when the temperature varied cannot give accurate values.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The error committed by the other models relative to the thermal model exceeds 25% with respect of Hamieh model. From Table , by taking the examples of the Kiselev method (γ s d (343.15 K ) = 57.8 mJ/m 2 )) and Hamieh model (γ s d (343.15 K) = 79.3 mJ/m 2 ), one obtained an error equal to . These results clearly showed that the various models that did not consider the change in the surface areas of molecules when the temperature varied cannot give accurate values.…”
Section: Resultsmentioning
confidence: 92%
“…The dispersive components of the surface energy of Ni-MOF-74 surfaces were determined using the Dorris–Gray method, the molecular models, and the thermal model. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations